The Role of New Media in Shaping Islamic Insights Among Generation Y and Z at Alauddin State Islamic University of Makassar - Saenal Abidin; Rasyid Masri; Firdaus Muhammad; Arifuddin Tike; Quraisy Mathar; Irvan Muliyadi; Das'ad Latif (Jurusan Ilmu Perpustakaan dan Informasi Islam Universitas Islam Negerin Datokarama Palu, 2026)
This study is motivated by the increasing use of new media in accessing Islamic information; however, studies explaining how such media contribute to the formation of Islamic knowledge at the individual level, particularly among Generation Y and Generation Z, remain limited. This study aims to analyze the role of new media in enhancing Islamic knowledge among Generation Y and Generation Z at Alauddin State Islamic University of Makassar. This research employs a qualitative approach with a descriptive design. Data were collected through in-depth interviews and Focus Group Discussions (FGDs) involving 11 informants, consisting of Generation Y lecturers and Generation Z students who actively use digital media. Data were analyzed using thematic analysis through coding, theme categorization, and conclusion drawing. The findings indicate that new media serve as a primary source for accessing Islamic knowledge through various digital platforms such as YouTube, Instagram, and Islamic websites. Generation Y tends to use new media functionally for academic purposes, while Generation Z utilizes it more intensively as part of their daily digital life. Moreover, new media encourage users to critically select and evaluate Islamic information. This study proposes the 4A Model (Access, Attention, Appraisal, and Adoption), which explains the stages of Islamic knowledge formation through new media. This model offers a conceptual contribution to understanding the mechanism of religious knowledge construction in the digital era. Abstrak Penelitian ini dilatarbelakangi oleh meningkatnya penggunaan media baru dalam memperoleh informasi keislaman, namun kajian yang menjelaskan bagaimana media tersebut berperan dalam pembentukan wawasan keislaman pada tingkat individu, khususnya pada Generasi Y dan Generasi Z, masih terbatas. Penelitian ini bertujuan untuk menganalisis peran media baru dalam menambah wawasan keislaman Generasi Y dan Generasi Z di Universitas Islam Negeri Alauddin Makassar. Penelitian ini menggunakan pendekatan kualitatif dengan desain deskriptif. Data dikumpulkan melalui wawancara mendalam dan Focus Group Discussion (FGD) terhadap 11 informan yang terdiri atas dosen Generasi Y dan mahasiswa Generasi Z yang aktif menggunakan media digital. Data dianalisis menggunakan analisis tematik melalui tahap pengkodean, pengelompokan tema, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa media baru dimanfaatkan sebagai sumber utama dalam memperoleh wawasan keislaman melalui berbagai platform digital seperti YouTube, Instagram, dan website keislaman. Generasi Y cenderung memanfaatkan media baru secara fungsional untuk kepentingan akademik, sedangkan Generasi Z menggunakannya secara lebih intensif sebagai bagian dari kehidupan digital sehari-hari. Selain itu, media baru mendorong proses seleksi dan evaluasi informasi keislaman secara kritis. Penelitian ini menghasilkan Model 4A (Access, Attention, Appraisal, dan Adoption) yang menjelaskan tahapan pembentukan wawasan keislaman melalui media baru. Model ini merupakan kontribusi konseptual dalam menjelaskan mekanisme pembentukan pengetahuan keagamaan di era digital.